ANALYSIS OF PHYSICOCHEMICAL AND ORGANOLEPTIC CHARACTERISTICS OF YELLOW PUMPKIN PUDDING (CUCURBITA MOSCHATA) - Putri, Diwyacitta Antya; Muyasyaroh, Hidayatun; Lukitasari, Febriani; Astuti, Nugrahani; Rerung, Novia Tesalonika Amanda; Ifadah, Raida Amelia (Universitas Veteran Bangun Nusantara, 2025)
Yellow pumpkin (Cucurbita moschata) is a nutrient-rich horticultural commodity with considerable potential for development into various food products, including pudding. However, scientific information regarding the effects of pumpkin incorporation on the physicochemical and sensory characteristics of pudding remains limited. This study aimed to evaluate the influence of different proportions of pumpkin (30%, 50%, and 70%) on the physicochemical properties, vitamin C content, and sensory acceptance of pumpkin pudding. A Completely Randomized Design (CRD) was employed with three replications for each treatment. The analyses included syneresis at two storage conditions (refrigerated and room temperatured), total dissolved solids (TDS), texture (hardness), color parameters (L*, a*, b*), vitamin C content determined by iodometric titration, and a hedonic test involving 30 untrained panelists. Data were analyzed using ANOVA followed by Duncan’s Multiple Range Test (DMRT) at a 5% significance level. The results showed that increasing the proportion of pumpkin had significant effects on TDS, texture, color attributes, vitamin C content, and most sensory parameters. Higher pumpkin concentrations decreased TDS and hardness values while increasing syneresis due to higher free-water content within the gel matrix. Lightness (L*) and vitamin C levels increased proportionally with the amount of pumpkin added. Sensory evaluation revealed that the 30% pumpkin formulation received the highest scores for color, aroma, texture, taste, and overall acceptance, whereas the 70% formulation received the lowest scores, particularly for color and chewiness. These findings indicate that the 30% pumpkin incorporation provides the most optimal balance of physical quality, nutritional enhancement, and consumer acceptability. Keywords: Organoleptic, Physicochemical Properties, Pudding, Pumpkin, Vitamin c